The performance of panel cointegration methods: Results from a large scale simulation study - Martin Wagner; Jaroslava Hlouskova (Institute for Advanced Studies (IHS), 2007)
This paper presents results concerning the performance of both single equation and system panel cointegration tests and estimators. The study considers the tests developed in Pedroni (1999, 2004), Westerlund (2005), Larsson, Lyhagen, and Löthgren (2001) and Breitung (2005); and the estimators developed in Phillips and Moon (1999), Pedroni (2000), Kao and Chiang (2000), Mark and Sul (2003), Pedroni (2001) and Breitung (2005). We study the impact of stable autoregressive roots approaching the unit circle, of I(2) components, of short-run cross-sectional correlation and of cross-unit cointegration on the performance of the tests and estimators. The data are simulated from three-dimensional individual specific VAR systems with cointegrating ranks varying from zero to two for fourteen different panel dimensions. The usual specifications of deterministic components are considered.
Keywords: C12; C15; C23; 330; cross-sectional dependence; estimator; panel cointegration; simulation study; test; Panel; Simulation; Kointegration; Statistischer Test; Schätztheorie; Theorie